![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
2个回答
展开全部
A^2 =
-2 -2√3
2√3 2
A^3 = AA^2 =
-8 0
0 -8
= -8E.
所以
当n = 3k 时, A^n = (A^3)^k = (-8E)^k = (-8)^kE
当n = 3k+1 时, A^n = A(A^3)^k = A(-8E)^k = (-8)^kA
当n = 3k+2 时, A^n = A^2(A^3)^k = A^2(-8E)^k = (-8)^kA^2 = (-8)^k *
-2 -2√3
2√3 2
-2 -2√3
2√3 2
A^3 = AA^2 =
-8 0
0 -8
= -8E.
所以
当n = 3k 时, A^n = (A^3)^k = (-8E)^k = (-8)^kE
当n = 3k+1 时, A^n = A(A^3)^k = A(-8E)^k = (-8)^kA
当n = 3k+2 时, A^n = A^2(A^3)^k = A^2(-8E)^k = (-8)^kA^2 = (-8)^k *
-2 -2√3
2√3 2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询